Respostas
respondido por:
2
2* x^2 = 72
2x^2 = 72
x^2 = 72/2
x^2 = 36
x = √36
x = 6
2x^2 = 72
x^2 = 72/2
x^2 = 36
x = √36
x = 6
respondido por:
2
Olá,
2x² = 72
x² = 72/2
x² = 36
x = √36
x = 6
ou
x = -√36
x = -6
Prova:
2(6)² = 2(36) = 72
2(-6)² = 2(36) = 72
Resposta:
6 ou -6
2x² = 72
x² = 72/2
x² = 36
x = √36
x = 6
ou
x = -√36
x = -6
Prova:
2(6)² = 2(36) = 72
2(-6)² = 2(36) = 72
Resposta:
6 ou -6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás